ON THE EXISTENCE OF [SnBu3Cl2]- IN (Cy2NH2)2C2O4•SnBu3Cl AND Cy2NH2O2PHPh•SnBu3Cl: A SPECTROSCOPIC CHARACTERIZATION - Alioune Fall; Dinora De Barros; Libasse Diop (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
On allowing (Cy2NH2)2C2O4•2H2O and Cy2NH2PhHPO2 to react with SnBu3Cl in ethanolic media, (Cy2NH2)2C2O4•SnBu3Cl and (Cy2NH2)O2PHPh•SnBu3Cl are obtained. Their spectroscopic studies mainly the Mössbauer technique, exhibit the presence of two tin (IV) centres allowing to consider the formulae as [SnBu3Cl2][SnBu3(C2O4)2][Cy2NH2]4 or [SnBu3Cl2][(SnBu3)2(PhHPO2)3][Cy2NH2]2 containing [SnBu3Cl2]- and [SnBu3(C2O4)2]3- or [(SnBu3)2(PhHPO2)3]- all three being dimeric entities with NH•••••Cl and NH•••••O hydrogen bonds involving the cations. The spectroscopic characterization of [SnBu3Cl2]- has been done for the first time in this work.